2023
DOI: 10.3390/nu15204373
|View full text |Cite
|
Sign up to set email alerts
|

Does the Protective Effect of Zinc on Telomere Length Depend on the Presence of Hypertension or Type 2 Diabetes? Results from the Iwaki Health Promotion Project, Japan

Mahiro Sato,
Kyi Mar Wai,
Ken Itoh
et al.

Abstract: Telomeres, repeated TTAGGG sequences at chromosomal ends, shorten with age and indicate cellular lifespan. Zinc can protect against telomere damage through its anti-oxidative effect. Meanwhile, telomere shortening was correlated with metabolic diseases of hypertension and type 2 diabetes. The objective of this study was to investigate whether the association between zinc and telomere length differs by the presence or absence of hypertension/type 2 diabetes. This is a cross-sectional study with 1064 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…46 Zinc supplementation reduces the production of proinflammatory factors such as TNF-α, IL-1β, and IL-6; inhibits oxidative stress; and increases the expression of the anti-inflammatory protein A20 in human monocytic leukemia (THP-1) cells and human aortic endothelial cells (HAECs). 47 Our experimental results showed that oxidative stress induced by sodium salicylate greatly increased the level of ROS in the gastric mucosa and activated the NF-κB signaling pathway, leading to the production of many inflammatory factors and intensifying inflammation. Zinc supplementation inhibits oxidative stress, regulates the NF-κB signaling pathway, reduces ROS levels, and inhibits the release of inflammatory factors such as TNF-α, IL-6, and IL-1β, thus alleviating inflammation.…”
Section: Discussionmentioning
confidence: 67%
“…46 Zinc supplementation reduces the production of proinflammatory factors such as TNF-α, IL-1β, and IL-6; inhibits oxidative stress; and increases the expression of the anti-inflammatory protein A20 in human monocytic leukemia (THP-1) cells and human aortic endothelial cells (HAECs). 47 Our experimental results showed that oxidative stress induced by sodium salicylate greatly increased the level of ROS in the gastric mucosa and activated the NF-κB signaling pathway, leading to the production of many inflammatory factors and intensifying inflammation. Zinc supplementation inhibits oxidative stress, regulates the NF-κB signaling pathway, reduces ROS levels, and inhibits the release of inflammatory factors such as TNF-α, IL-6, and IL-1β, thus alleviating inflammation.…”
Section: Discussionmentioning
confidence: 67%